Lematização de unidades fraseológicas diacríticas em dicionários bilíngues espanhol/português - Simao, Angelica Karim Garcia [UNESP] (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2014)
In this paper we consider a broad conception of phraseology to propose a description and analysis of phraseological units of stemming diacritical Spanish / Portuguese bilingual dictionaries. The focus of the analysis seeks to show not only the organization of the macro-structure proposed by two different lexicographical works, but also to discuss the use of labels and equivalences presented. Phraseological units are understood here as diacritical phraseologisms containing unique lexias, lacking syntactic and semantic autonomy recognized by speaker only within fixed expressions.

Neste trabalho partimos de uma concepção ampla de fraseologia para propor a descrição e análise da lematização de unidades fraseológicas diacríticas em dicionários bilíngues espanhol/português. O foco do trabalho busca evidenciar não só a organização da macroestrutura proposta por duas obras lexicográficas diferentes, como também discutir as marcas de uso e equivalências apresentadas. Unidades fraseológicas diacríticas são entendidas no presente trabalho como fraseologismos que contêm lexias únicas, carentes de autonomia sintática e semântica, reconhecidas pelo falante somente dentro de expressões fixas.
Stemming from diacritical phraseological units in bilingual dictionaries Spanish/Portuguese
Keywords: Metalexicografia; Fraseologia bilíngue; Unidades fraseológicas diacríticas; Língua espanhola; Metalexicography; Bilingual phraseology; Diacritical phraseological units; Spanish language